The interactions of international relations: racism, colonialism, producer-centred research - Datta-Ray, Deep K. (2023)
The racial hierarchy underscoring colonialism persists, organises core-periphery interactions and so undermines International Relations’ (IR’s) purpose of accounting and explaining to mitigate violence. Despite IR’s awareness of its colonialism, it reconstitutes in the hermeneutic’s deductive and inductive method via aphasia (calculated forgetting) about its heuristic: diplomacy. The result, analytic-violence or the core’s heuristic corrupting interaction with the periphery. Yet, its evasiveness testifies to a meaningfulness beyond IR’s hermeneutic. Irretrievably corrupted by its heuristic, IR’s hermeneutic is ejected for an altogether new hermeneutic: Producer-Centred Research (PCR). Eschewing deduction and induction, and so colonialism, PCR initiates with abduction or a problem arising from theory and practice to resolve it in terms of rationality because of its, and the problem’s, significance. Changing “rationality” to “rationalities” registers the core’s rationality as colonialism while preventing it from contaminating PCR’s collection and assessment of peripheral practices to determine if they cohere into another rationality. Moreover, treating peripheral practitioners authoritatively, as capable of rationalising themselves and thus equal to rationality, further protects PCR from aphasia. Verifying efficacy shows PCR’s decolonisation of the hermeneutic is not entirely replicated externally, amongst IR scholars. The core engages PCR, but it incites violence in the periphery which defends rationality and so is colonialism’s bastion, now.